2007
DOI: 10.1080/10635150701703063
|View full text |Cite
|
Sign up to set email alerts
|

Adding More Ecology into Species Delimitation: Ecological Niche Models and Phylogeography Help Define Cryptic Species in the Black Salamander (Aneides flavipunctatus)

Abstract: Being able to efficiently and accurately delimit species is one of the most basic and important aspects of systematics because species are the fundamental unit of analysis in biogeography, ecology, and conservation. We present a rationale and approach for combining ecological niche modeling, spatially explicit analyses of environmental data, and phylogenetics in species delimitation, and we use our methodology in an empirical example focusing on Aneides flavipunctatus, the black salamander (Caudata: Plethodont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
379
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 419 publications
(403 citation statements)
references
References 69 publications
7
379
0
5
Order By: Relevance
“…genetic drift, mutations) or by divergent selection [2,25]. Longer periods of isolation are expected to increase ecological differentiation/divergence [26,27], and this has been demonstrated in several taxa [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…genetic drift, mutations) or by divergent selection [2,25]. Longer periods of isolation are expected to increase ecological differentiation/divergence [26,27], and this has been demonstrated in several taxa [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the proposed species boundaries within the P. coronatum complex occur at junctions separating different ecological regions in Baja California (7), which implies that ecological diversification has played a critical role during lineage formation in this system. Ecological divergence represents an important stage during the process of lineage separation that has become increasingly feasible to quantify by using geographical information systems (GIS), and it is furthermore now possible to integrate these data within a phylogeographic framework (8)(9)(10). Predicting the geographic distributions of lineages can help to identify barriers to dispersal that are important because they can restrict gene flow and facilitate population divergence on an evolutionary timescale (11).…”
mentioning
confidence: 99%
“…31). In the Salamandridae, vicariant species formation appears to be the rule, as exemplified in many cases studies: (32)(33)(34)(35)(36). Nonadaptive species formation, fragmentation of an ancestral species range with niche conservation through time, was suggested to explain the ecological similarity of plethodontid salamanders in California (7).…”
Section: Evolution Of Niches and Geographic Ranges: Patterns Vs Procmentioning
confidence: 99%
“…Nonadaptive species formation, fragmentation of an ancestral species range with niche conservation through time, was suggested to explain the ecological similarity of plethodontid salamanders in California (7). Information on observed spatial patterns in relation to climate envelopes is increasingly used in studies of species formation (5,15,36). For example, comparisons of the distribution and environmental suitability between sister pairs of species of montane plethodontid salamanders suggested that niche conservatism may promote allopatric species formation (5).…”
Section: Evolution Of Niches and Geographic Ranges: Patterns Vs Procmentioning
confidence: 99%